Bromine-terminated azobenzene liquid crystals. Issue 5 (9th April 2019) - Sanches, Sergio A. A.; Costa, Wallison C.; Bechtold, Ivan H.; Halfen, Renato A. P.; Merlo, Aloir A.; Campo, Leandra F.
ABSTRACT: A series of liquid crystals (LCs) of bromine-terminated azobenzene were synthesised and characterised. The LCs were composed of an azobenzene core, an alkyl chain and a flexible spacer with a bromine atom at a remote position. Mesomorphic properties were dependent on both the alkyl chain length and the relative position of the bromine atom at the end of the spacer group. The nematic phase was favoured over the smectic A phase for alkyl chains with one and seven carbon atoms. However, the SmA mesophase was dominant for compounds with 10-carbon alkyl chains. The remote bromine atom in the spacer group favoured SmA for homologous with n -decyl chains and the nematic phase for n -heptyl and methyl groups. Molecular modelling showed that the azobenzene LCs tended to adopt the all trans -conformation in the gas phase as the number of carbon atoms increased. For short spacer groups, bent conformations contributed to the level population proportion of conformers. For the non-LC 5a, the gauche conformation became the most stable with a torsional angle of –68.9°. X-ray experiments showed a monolamellar SmA mesophase in an antiparallel arrangement. Absorption maxima at 360 and 440 nm were assigned to π–π* and n–π* transitions, respectively. Graphical Abstract: